Electrokinetics Remediation of Mercury Contaminations of Bandar Imam Petrochemical Complex of Iran - Goudarzi Nik, M.; Shahbazi, B.; Naserian, S. (Asian Journal of Chemistry, 2013)
In this research, electrokinetics remediation of the mercury contaminations from Bandar Imam petrochemical complex was investigated. The research was run with two types of soils containing (1) sediment samples collected from Bandar Imam petrochemical complex and (2) sand and clay mixture (1:2 ratio) artificially contaminated to mercury. The mercury concentration of the Bandar Imam petrochemical complex and sand and clay samples was 110 and 98 ppm, respectively. The removal process was monitored both at 1 and 1.5 V/cm2 voltage gradients. The results demonstrated that 0.4 M potassium iodide solution with 1 V/cm2 had a higher efficiency than the one 1.5 V/cm2 with an average removal of 49.1 and 60.2 % for the Bandar Imam petrochemical complex and sand and clay samples, respectively. Other parameters involved such as pH of both the cathode and anode reservoirs, total pH of the cell during the process, amperage and optimum moisture content during the process were considered as well.